V=12
Equation: v=-3(-1-3)
V=-3(-4)
V=12
Answer:
y = 4x-3
Step-by-step explanation:
First we need to determine the slope
Using two points on the line (0,-3) (1,1)
Using the slope formula
m = (y2-y1) /(x2-x1)
= (1- -3)/(1-0)
(1+3)/ (1-0)
4
We know the y intercept, -3
y = mx+b where m is the slope and b is the y intercept
y = 4x-3
If f(x)=69-15x then ![f(f^{-1}(x))=x](https://tex.z-dn.net/?f=f%28f%5E%7B-1%7D%28x%29%29%3Dx)
Given :
![f(x)=69-15x\\](https://tex.z-dn.net/?f=f%28x%29%3D69-15x%5C%5C)
Lets find out
. The steps to find out f inverse are
Replace f(x) by y
![y=69-15x\\Interchange \; the \; variables\\x=69-15y\\solve \; for \; y\\x-69=-15y\\Divide \; by \; -15\\\frac{-x+69}{15} =y\\Replace \;y \;with \; f^{-1}\\f^{-1}=\frac{-x+69}{15}](https://tex.z-dn.net/?f=y%3D69-15x%5C%5CInterchange%20%5C%3B%20the%20%5C%3B%20variables%5C%5Cx%3D69-15y%5C%5Csolve%20%5C%3B%20for%20%5C%3B%20y%5C%5Cx-69%3D-15y%5C%5CDivide%20%5C%3B%20by%20%5C%3B%20-15%5C%5C%5Cfrac%7B-x%2B69%7D%7B15%7D%20%3Dy%5C%5CReplace%20%5C%3By%20%5C%3Bwith%20%5C%3B%20f%5E%7B-1%7D%5C%5Cf%5E%7B-1%7D%3D%5Cfrac%7B-x%2B69%7D%7B15%7D)
Now we find ![f(f^{-1}(x))](https://tex.z-dn.net/?f=f%28f%5E%7B-1%7D%28x%29%29)
Replace inverse function in the place of x in f(x)
![f(f^{-1}(x))=f(\frac{-x+69}{15} )=69-15(\frac{-x+69}{15})=69-(-x+69)=69+x-69=x\\f(f^{-1}(x))=x](https://tex.z-dn.net/?f=f%28f%5E%7B-1%7D%28x%29%29%3Df%28%5Cfrac%7B-x%2B69%7D%7B15%7D%20%29%3D69-15%28%5Cfrac%7B-x%2B69%7D%7B15%7D%29%3D69-%28-x%2B69%29%3D69%2Bx-69%3Dx%5C%5Cf%28f%5E%7B-1%7D%28x%29%29%3Dx)
Learn more :
brainly.com/question/11242094
The answr is 2 okay that’s the answer
Answer:
b) 1000x + 115
Step-by-step explanation:
C = 20y + 15
= 20(50x + 5) + 15
= 1000x + 100 + 15
= 1000x + 115